Вышивка крестом. Большая коллекция узоров - Миронова Татьяна Владимировна (Мир книги, 2008)
Экземпляры: аб. (20250217) / Инвентарный номер: 65557 / Цена: / Сис.шифр: 37.248 / Авт.знак: М 64 / ГРНТИ: 75.35 / ББК: 37.248